A fatal yarn - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery., 2020)
The trees in Arborville, New Jersey, have started sporting sweaters. Part of the trend of public knitting art? Not exactly. An anonymous activist has been wrapping trunks in yarn to cover red X's that mark certain trees for removal by the town so they don't interfere with power lines. When the town's mayor<U+2014>who supports cutting down the trees<U+2014>is murdered, Pamela wonders if the tree hugger committed homicide to prevent arborcide. A knitter is arrested, but it's one of Knit and Nibble's own<U+2014>the harmless Roland DeCamp, who was seen arguing with the mayor. Pamela is sure the police are barking up the wrong tree. With the help of her reporter friend Bettina, she branches off on her own investigation to root out the real killer . . .